PENGARUH TERPAAN ELECTRONIC WORD OF MOUTH MELALUI TECH REVIEWER YOUTUBE (GADGETIN) DAN CITRA MEREK TERHADAP MINAT BELI SMARTPHONE REALME - Rohmat Pambudi; Tandiyo Pradekso (Interaksi Online, 2022)
Based on a global survey conducted by the research institute Nielsen with 28,000 respondents in 56 countries including Indonesia. The results show that recommendations from consumers submitted online, including one of the trusted advertising sources with a percentage of 70%. One of these activities is smartphone reviews, as done by GadgetIn. Review is one form of electronic word of mouth / eWoM communication that can affect the selling value of a product. Realme, a smartphone company from China, experienced a decline in sales and its brand image was not included in the top 5 smartphone brands in Indonesia. The purpose of this study was to determine the effect of eWOM exposure through YouTube's tech reviewer (GadgetIn) and brand image on interest in buying Realme smartphones. This study uses the Traditional Word of Mouth Theory proposed by George Silverman to explain the effect of X1 on Y. Then, to explain the effect of X2 on Y, Martin Fishbein uses Reasoned Action Theory. Sampling in this study was conducted using a non-robability sampling technique with purposive sampling. The population in this study is the people of Semarang City who actively use YouTube social media and are 18-24 years old. Data analysis was performed using simple linear regression to test the first and second hypotheses. The results of the hypothesis test show that there is an effect of exposure to eWOM through YouTube technology reviewers (GadgetIn) on interest in buying a Realme smartphone, which has a significance of 0.000 and an R Square value of 0.257 or 25.7%. This means that the hypothesis can be proven and the word of mouth theory can be tested. Then in the second hypothesis, it is tested that there is an influence of brand image on interest in buying a Realme smartphone with a significance value of 0.000 and an R Square value of 0.744 or 74.4%. Not only that, the theory of reasoned action can be proven